2012
DOI: 10.1063/1.3698341
|View full text |Cite
|
Sign up to set email alerts
|

Very low bias stress in n-type organic single-crystal transistors

Abstract: Bias stress effects in n-channel organic field-effect transistors (OFETs) are investigated using PDIF-CN 2 single-crystal devices with Cytop gate dielectric, both under vacuum and in ambient. We find that the amount of bias stress is very small as compared to all (p-channel) OFETs reported in the literature. Stressing the PDIF-CN 2 devices by applying 80 V to the gate for up to a week results in a decrease of the source drain current of only ~1% under vacuum and ~10% in air. This remarkable stability of the de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In particular, trap states, which can be induced by residual charge density in the dielectric or active layer, influence the threshold voltage, mobility, and hysteresis in the transfer characteristics. Therefore, a lot of effort have been devoted to finding a thin dielectric and organic single crystals active layer that can maintain high interface quality in combination with high gate efficiency to improve the performance of OFETs In particular p‐ or n‐types single crystal semiconducting active layers including rubrene, pentacene, tatracene, triisopropylsilylethynylpentacene (TIPS‐pentacene), poly(3‐hexylthiopene) (P3HT), N , N 0‐bis(n‐alkyl)‐(1,7 and 1,6)‐dicyanoperylene‐3,4:9,10‐bis(dicarboximide)s (PDIF‐CN2), tetracyanoquinodimethane (TCNQ), fullerene and others, have excellent device properties when combined with dielectrics such as air‐gap, polydimethylsiloxane (PDMS), CYTOP, and polymeric materials . Newly developed dielectrics can preserve the high channel mobility of single crystal active layers by eliminating the interface defects.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, trap states, which can be induced by residual charge density in the dielectric or active layer, influence the threshold voltage, mobility, and hysteresis in the transfer characteristics. Therefore, a lot of effort have been devoted to finding a thin dielectric and organic single crystals active layer that can maintain high interface quality in combination with high gate efficiency to improve the performance of OFETs In particular p‐ or n‐types single crystal semiconducting active layers including rubrene, pentacene, tatracene, triisopropylsilylethynylpentacene (TIPS‐pentacene), poly(3‐hexylthiopene) (P3HT), N , N 0‐bis(n‐alkyl)‐(1,7 and 1,6)‐dicyanoperylene‐3,4:9,10‐bis(dicarboximide)s (PDIF‐CN2), tetracyanoquinodimethane (TCNQ), fullerene and others, have excellent device properties when combined with dielectrics such as air‐gap, polydimethylsiloxane (PDMS), CYTOP, and polymeric materials . Newly developed dielectrics can preserve the high channel mobility of single crystal active layers by eliminating the interface defects.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, PDI_CY n-type OFET, exhibiting charge carrier mobility higher than 1 cm 2 /Volt sec [ 11 , 12 ] are among the most studied devices in the emerging field of organic electronics [ 5 ] . PDI_CY semiconducting films exhibit also a strong interaction with light and the electrical response of the related devices can be so largely modified through the illumination by visible radiation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides analyzing the BS response of devices based on SiO 2 , in our studies, we also assessed the behavior of PDIF-CN 2 transistors employing the fluoro-polymer Cytop TM as a dielectric. In a first report [31], the BS effect was investigated for PDIF-CN 2 single-crystal transistors demonstrating how the combination between a crystalline active layer and a highly hydrophobic dielectric surface allows for achieving n-type devices with very low sensitivity to BS. For an experiment carried out in air, we found that the I DS current was decreased by only 10% under the application of a positive V GS for an entire week (≈ 6 × 10 5 s).…”
Section: Proton Migration Model For N-type Devicesmentioning
confidence: 99%
“…Different from PDI8-CN 2 , PDIF-CN 2 has been used even to grow high-quality single crystals, exhibiting remarkable performances in terms of mobility values and operation stability under ambient conditions [27][28][29]. The research group lead by Alberto Morpurgo at the University of Geneva carried out very accurate studies on PDIF-CN 2 single-crystal transistors turning this compound into the reference material for analyzing the fundamental properties of electron-transporting organic semiconductors [30,31]. PDIF-CN 2 single crystals were usually fabricated by laminating thin (<1 µm) crystals on different back-gated substrates, bearing a dielectric barrier and pre-patterned gold electrodes.…”
Section: Introductionmentioning
confidence: 99%